Answer :

Given


The above inequality can be split into two inequalities.


and


Let us consider the first inequality.



As x > 0, we have x + 1 > 0.



4 ≤ 3(x + 1)


4 ≤ 3x + 3


3x + 3 ≥ 4


3x + 3 – 3 ≥ 4 – 3


3x ≥ 1




(1)


Now, let us consider the second inequality.



As x > 0, we have x + 1 > 0.



3(x + 1) ≤ 6


3x + 3 ≤ 6


3x + 3 – 3 ≤ 6 – 3


3x ≤ 3



x ≤ 1


x (–∞, 1] (2)


From (1) and (2), we get




Thus, the solution of the given system of inequations is


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics